Comparison of Disk Diffusion and Agar Dilution Method for the Detection of Mupirocin Resistance in Staphylococcal Isolates from Skin and Soft Tissue Infections - Shivanna, Vijaya; Dasegowda, Venkatesha (Journal of Laboratory Physicians, 2023)
Aims and Objectives Mupirocin is a widely used topical antibiotic for the treatment of skin and soft tissue infections. This has resulted in resistance leading to treatment failure. Hence, the present study aimed to determine the prevalence of mupirocin resistance among staphylococcal isolates obtained from the skin and soft tissue infections. Also, comparison of disc diffusion and agar dilution method in detecting mupirocin resistance was done.Materials and Methods This cross-sectional study was conducted in the Department of Microbiology of a tertiary health care center in Karnataka from January to December, 2018. Clinical samples such as wound swabs, tissues, and pus were included in the study. All staphylococcal isolates were screened for mupirocin resistance using 5 µg and 200 µg discs for low-level (MuL) and high-level mupirocin resistance (MuH), respectively. Minimum inhibitory concentration (MIC) was determined using the agar dilution method.Results Out of 100 staphylococcal isolates, 68 were Staphylococcus aureus and 32 were CoNS. MuH was detected in 11 isolates. MuH was more common in CoNS (10/11) compared with S. aureus (1/11). MuL was not found in the study.Discussion In our study, 10 out of 11 mupirocin-resistant isolates were methicillin resistant, which is statistically significant (p < 0.05). The correlation between results of disc diffusion and MIC were appropriate in this study.Conclusion Judicial prescription of mupirocin after knowing the susceptibility report should become the standard practice. Screening for mupirocin resistance can be done by disc diffusion in resource-limited settings.
Keywords: mupirocin; low-level resistance; high-level resistance; disc diffusion; agar dilution